Pelatihan Pembuatan Balsam Stik Dari Bahan Herbal Dan Perintisan Sebagai Home Industri - dwi - Ningsih; Sri Rejeki Handayani; Ismi - Rahmawati; Dewi - Ekowati; Desi - Purwaningsih (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
Balm, a pharmaceutical product that is no stranger to the community, therefore, this product is one of the most potential commodities developed into a home industry that can improve the economy of the community. relatively simple balm formulation and easy in material, is very possible to be applied in the community. This article is a form of publication of community service that has been carried out on Tuesday, February 6, 2018,at RW XXII Bibis Luhur Kel. Nusukan Kec. Banjarsari Surakarta Central Java. This community service is entitled